PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL - Prasetyo, Irvan Fendy; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen; Vol 9 No 2 (2020)DO - 10.24843/EJMUNUD.2020.v09.i02.p08, 2020)
The purpose of this study is to determine the stocks of the Kompas 100 Index that can form optimal portfolios and to find out the proportions of each selected stock and the level of return and risk of the resulting portfolio. Single Index Model with descriptive analysis was used. The data was obtained from the IDX, Yahoo Finance, and BI. The population in this study amounted to 77 shares. The number of samples taken was 65 company shares from the Kompas 100 Index, using the Slovin method. Based on the results of the analysis obtained from 65 shares of Kompas 100 members obtained a combination of 20 shares that can form an optimal portfolio of BUMI, MAPI, INCO, DOID, INDY, CPIN, BKSL, ACES, MEDC, ITM, UNTR, TINS, BDMN, JPFA, BBCA, BJBR, PNBN, TARA, PBRX and ANTM with portfolio expected return of 3.20 percent with a risk of 0.11 percent. Keywords: Compass 100 Index, Single Index Model, Optimal Portfolio